From Green to Gold and back? Adventures and (re)routings on the way to full Open Access - Šimukovič, Elena (Septentrio Conference Series, 2017)
Watch the VIDEO here. Since the “Amsterdam Call for Action on Open Science” was published in April 2016, there is supposed to be “a clear panEuropean target: from 2020 all new publications are available through open access from the date of publication”. This call falls into a line of events, in which demands for a more rapid or even radical transition towards full Open Access world experienced a considerable accumulation. With the “OA2020” initiative launched shortly before and the conclusions on the transition towards an Open Science system adopted by the Council of the European Union in late spring of the same year the whirl of excitement seemed to reach its peak. Yet more than a year later a universal consensus on a “one size fits all”-type solution as proposed by a widely debated and promoted white paper of the Max Planck Digital Library has still to prevail. Not only have country or institution-specific case studies which set out for a challenge to quantify potential benefits and disadvantages of such a scenario for themselves delivered mixed results and propositions. Some of the “most eminent” research institutions and nations seem to even back track from their initially stringent Gold-only Open Access transition roadmaps. Unsurprisingly, long-standing Open Access advocates and scholars like Stevan Harnad and Jean-Claude Guédon have repeatedly pointed out that Green, Gold and any other new alternative Open Access models should be seen as complementary strategies and encouraged further experimentation with respect to flexibility and adaptation to local circumstances. Thus, this talk will try to address the perceived “either-or” dilemma in many of recent initiatives and to take a closer look at some of their arguments and underlying assumptions. What it is expected to deliver will be a rather more differentiated and colourful picture of current Open Access transitions and visions.